Aluminum metal negative electrode material with dynamic alloy coating as well as preparation and application of aluminum metal negative electrode material

By using dynamic alloy coating aluminum metal negative electrode material in aluminum ion batteries, a uniform deposition morphology is formed using aluminum-manganese/aluminum-magnesium-based alloys and nicotinic acid, the polarization problem caused by hydrogen evolution reaction and passivation in aluminum ion batteries is solved. , achieve long cycle stability and high Coulomb efficiency, avoid battery short circuits, and simplify process flow.

CN119324202APending Publication Date: 2025-01-17BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449371.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

During the charging and discharging process, aluminum ion batteries have polarized the negative electrode of aluminum metal due to side reactions such as hydrogen evolution reaction and passivation. Coulomb's efficiency is low, and the traditional electronic conductor interface layer fails during the cycle, resulting in battery short-circuit problem.

Method used

Aluminum metal negative electrode material with dynamic alloy coating is used. By adding aluminum-manganese/aluminum-magnesium-based alloys and nicotinic acid to the electrolyte, a uniform deposition morphology is formed, which avoids the failure of the electronic conductor layer being covered and improves the corrosion resistance of the alloy phase. sex.

Benefits of technology

The long cycle stability and high Coulomb efficiency of aluminum ion batteries are achieved, and the battery short circuit is avoided, and the process is simple and easy to promote has commercial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324202A_ABST
    Figure CN119324202A_ABST
Patent Text Reader

Abstract

The invention relates to a co-deposition aluminum alloy negative electrode material as well as preparation and application thereof, and belongs to the technical field of aluminum ion batteries. The negative electrode material is a two-dimensional / three-dimensional current collector material with an electric co-deposition aluminum-manganese / aluminum-magnesium-based alloy layer on the surface. The alloy layer has good electronic conductivity and excellent aluminum affinity, is dynamically formed / deconstructed along with the cycle process of the battery, and is not easy to fail due to coverage of an aluminum deposition layer in the cycle process, so that the long cycle performance of the aluminum ion battery is remarkably improved, and the service life of the battery is prolonged. Therefore, the negative electrode material has a good application prospect as the negative electrode material of the ionic liquid-based aluminum ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum metal negative electrode material with a dynamic alloy coating, preparation and application thereof, and belongs to the technical field of aluminum ion batteries. Background Art

[0002] The rapid development of the economy and society has brought new challenges to energy storage technology. Secondary batteries with high safety, high specific energy, environmental friendliness and low cost have attracted extensive attention. Aluminum-ion batteries usually use abundant aluminum metal as the negative electrode material and have a high volumetric capacity (8046 mAh / cm 3 ). In addition, the high safety of aluminum-ion batteries makes them promising for large-scale energy storage. However, aqueous aluminum-ion batteries are accompanied by a strong hydrogen evolution reaction (HER) during the charging and discharging process; and side reactions such as corrosion and passivation of the aluminum metal negative electrode interface will aggravate the polarization of the aluminum metal negative electrode, resulting in lower coulombic efficiency and aluminum metal utilization. In recent years, the development of room temperature ionic liquid electrolyte systems represented by electrolytes composed of aluminum chloride (AlCl3) and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) has greatly promoted the development of aluminum-ion batteries and achieved reversible electroplating / stripping of metallic aluminum. However, although room temperature ionic liquid electrolytes avoid problems such as HER and passivation, the battery short circuit problem caused by aluminum dendrite growth has brought new challenges to the development of aluminum-ion batteries under this system.

[0003] In order to solve the above problems, researchers often modify the surface of aluminum metal negative electrode with an aluminophilic interface layer with good electron transfer performance. This electronic conductor interface layer can effectively improve the charge transfer performance of the electrode / electrolyte interface, regulate the uniform nucleation of aluminum metal with aluminophilic sites, and promote uniform deposition. However, for the aluminum metal negative electrode modified by the electronic conductor interface layer, the electron transfer process occurs at the interface between the electronic conductor interface layer and the electrolyte, that is, the deposition of aluminum metal will occur on the surface of the electronic conductor interface layer. As the cycle proceeds, the aluminophilic electronic conductor interface layer will be covered by aluminum metal, causing the aluminophilic electronic conductor interface layer to fail. Aluminum-based alloys usually have good aluminophilicity, so alloying the negative electrode is an effective strategy to achieve reversible electroplating / stripping of aluminum metal. At present, the alloying strategy for aluminum metal negative electrodes is mainly the melt co-casting method. However, this alloy negative electrode production process will consume a lot of energy. Summary of the invention

[0004] Based on the challenges currently faced by aluminum alloy negative electrode materials, the present invention provides an aluminum metal negative electrode material with a dynamic alloy coating, its preparation and application. Since the aluminum-manganese / aluminum-magnesium-based alloy has good aluminum affinity, the first formed aluminum-manganese / aluminum-magnesium alloy can be used as an aluminum affinity site to induce uniform nucleation of aluminum metal, and finally obtain a uniform deposition morphology. In addition, the room temperature ionic liquid-based electrolyte has strong corrosiveness, and the doping of manganese (Mn) or magnesium (Mg) elements can effectively improve the corrosion resistance of the alloy phase, thereby improving the interface stability of the aluminum metal negative electrode. The addition of nicotinic acid additives in the ionic liquid electrolyte promotes the growth and deposition of the deposition layer along the substrate plane; the addition of nicotinic acid can also effectively increase the metal aluminum nucleation energy barrier, thereby reducing the grain size of the metal aluminum and avoiding the formation of coarse aluminum dendrites. The preparation process of the dynamic alloy coating is simple. It only needs to add alloying components and additives to the electrolyte to realize the dynamic electroplating / stripping of the alloy coating during the battery cycle charge and discharge process, which can avoid the problem of failure caused by being covered by deposited aluminum faced by the traditional electronic conductor layer. The aluminum metal negative electrode material with dynamic alloy coating is applied to aluminum ion batteries, showing excellent electrochemical performance. In addition, the material preparation process is simple, easy to promote, and has good commercial prospects.

[0005] The objectives of the present invention are achieved through the following technical solutions.

[0006] An aluminum metal negative electrode material with a dynamic alloy coating consists of a two-dimensional current collector or a three-dimensional current collector and an aluminum metal and aluminum-manganese / aluminum-magnesium based alloy layer on the surface.

[0007] Furthermore, the two-dimensional current collector is titanium foil, molybdenum foil, tantalum foil and aluminum foil, and the three-dimensional current collector is carbon cloth, carbon paper, titanium mesh and molybdenum mesh.

[0008] Furthermore, the composition of the aluminum-manganese alloy layer is Al6Mn.

[0009] A method for preparing an aluminum metal negative electrode material with a dynamic alloy coating comprises the following steps:

[0010] (1) In a glove box filled with argon, aluminum chloride (AlCl3) and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) are prepared into a solution in a certain molar ratio, and then alloying element metal salt and nicotinic acid additive are added to the solution, and magnetic stirring is performed until a transparent and clear mixed solution is obtained.

[0011] (2) Assembling a CR 2032 button-type battery using the two-dimensional / three-dimensional current collector as the positive and negative electrodes, the mixed solution prepared in step (1) as the electrolyte, and glass fiber as the separator.

[0012] (3) Using graphite as the positive electrode material, the two-dimensional / three-dimensional current collector as the negative electrode, the mixed solution prepared in step (1) as the electrolyte, glass fiber as the separator, and molybdenum foil to separate the positive electrode material and the gasket, assembling a CR 2032 button-type full battery.

[0013] Furthermore, in step (1), the molar ratio of AlCl3 to [EMIm]Cl is 0.5 to 2:1.

[0014] Furthermore, the alloying element source metal salt in step (1) is MnCl2, MnSO4, Mn(ClO4)2, Mn(NO3)2, MgCl2, MgSO4, Mg(ClO4)2 and Mg(NO3)2.

[0015] Furthermore, in step (1), the concentration of the alloying element metal salt is 5 mM to 100 mM.

[0016] Furthermore, in step (1), the mass concentration of the nicotinic acid additive is 0.5% to 4%.

[0017] An aluminum metal negative electrode material with a dynamic alloy coating is used as a negative electrode in a room temperature ionic liquid electrolyte aluminum ion battery.

[0018] Beneficial effects:

[0019] (1) In the process of preparing the aluminum metal negative electrode material with dynamic alloy coating described in the present invention, the molar ratio of AlCl3 to [EMIm]Cl should not be too high or too low. If the concentration of AlCl3 is too low, the ionic conductivity of the electrolyte will be significantly reduced, which will in turn cause the kinetic behavior to be delayed, the battery's ability to respond to current will be significantly reduced, and the rate performance will be reduced; if the concentration of AlCl3 is too high, the electrolyte's ability to dissolve alloying element metal salts and nicotinic acid additives will be significantly reduced, and an electrolyte system that can achieve dynamic electrodeposition of alloy coatings cannot be formed.

[0020] (2) In the process of preparing the aluminum metal negative electrode material with dynamic alloy coating described in the present invention, the metal cations in the alloying element metal salt used will become the components of the co-deposited alloy coating, and are used to construct the dynamic alloy coating. The salt concentration should not be too high or too low. If the concentration of the alloying element metal salt is too low, the number of aluminum-philic alloy sites formed on the substrate in the initial deposition stage will be too small, which is insufficient to promote the uniform deposition of aluminum metal; if the concentration of the alloying element metal salt is too high, the charge transfer rate at the electrode interface will be significantly reduced, the electrode polarization will increase, and it will be difficult for the battery to obtain stable long-cycle performance.

[0021] (3) In the process of preparing the aluminum metal negative electrode material with dynamic alloy coating described in the present invention, the nicotinic acid additive used can increase the metal aluminum nucleation energy barrier, reduce the grain size of the electro-co-deposited alloy coating, promote uniform nucleation of the alloy phase, and help avoid the growth of aluminum dendrites. The nicotinic acid concentration should not be too high or too low. If the nicotinic acid concentration is too low, the deposited grains cannot be effectively refined, and the growth morphology of sharp aluminum dendrites cannot be effectively improved; if the nicotinic acid concentration is too high, the electrochemical co-deposition kinetics are sluggish, making it difficult to complete the normal electrochemical deposition process, and it is even more impossible to prepare a dynamic alloy coating by electrochemical co-deposition.

[0022] (4) The aluminum metal negative electrode material with dynamic alloy coating described in the present invention has a simple preparation process, is easy to promote, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the scanning electron microscope (SEM) image of 1#AlMn prepared in Example 1.

[0024] Figure 2 This is the X-ray diffraction (XRD) pattern of 1#AlMn prepared in Example 1.

[0025] Figure 3 The SCell-1 and SCell-0 assembled in Example 1 and Comparative Example 1 were respectively assembled at a current density of 0.5 mA cm -2 , capacity is 0.5 mAh cm -2 Cycle performance diagram when .

[0026] Figure 4 The SCell-1 and SCell-0 assembled in Example 1 and Comparative Example 1, respectively, were subjected to a current density of 1 mA cm -2 , capacity is 1 mAh cm -2 Cycle performance diagram when .

[0027] Figure 5 FCell-1 and FCell-0 assembled in Example 1 and Comparative Example 1, respectively, at 1Ag -1 Cyclic performance diagram obtained at a current density of .

[0028] Figure 6 This is the SEM image of 0#AlAl prepared in Comparative Example 1. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0030] In the following embodiments:

[0031] SEM characterization: A field emission scanning electron microscope (Hitachi SU-7) was used to observe the microstructure of the samples with an accelerating voltage of 5.0 kV.

[0032] Assembly of CR 2032 pair batteries: Aluminum foil is used as positive and negative electrodes, glass fiber is used as a separator, and the electrolyte is 80 μL of the prepared mixed solution to assemble the pair batteries.

[0033] Electrochemical performance test: The CR 2032 battery was tested for cycle performance using the Land test system, and the test data was recorded using software.

[0034] Preparation method of positive electrode material: Using N-methylpyrrolidone (NMP) as solvent, graphite and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 9:1 to obtain positive electrode slurry, and the positive electrode slurry is coated on carbon paper using a scraper, placed in an oven at 80°C for overnight drying, and punched to obtain a graphite positive electrode sheet.

[0035] Example 1

[0036] (1) In a glove box filled with argon, AlCl3 and [EMIm]Cl were prepared into a solution at a molar ratio of 1.3:1, and then the solution was prepared into a clear and transparent mixed solution with a MnCl2 concentration of 10 mM and a nicotinic acid concentration of 2% (mass fraction).

[0037] (2) Using aluminum foil as the negative electrode, the mixed solution prepared in step (1) as the electrolyte, and glass fiber as the separator, a CR 2032 button cell was assembled and named SCell-1.

[0038] (3) Using graphite as the positive electrode, aluminum foil as the negative electrode, the mixed solution prepared in step (1) as the electrolyte, glass fiber as the separator, and molybdenum foil to separate the positive electrode material and the gasket, assemble a CR 2032 button-type full battery, named FCell-1.

[0039] Take SCell-1 as the sample and set 1mA cm -2 The discharge current density is 3 mAh cm -2 The deposition capacity of the positive electrode aluminum metal electrode material modified by the electro-co-deposition alloy coating was named 1#AlMn. The SEM test was used to characterize the microscopic morphology of the alloy coating on the surface of the positive electrode aluminum foil. Figure 1 The test results show that the alloy phase coating obtained in this embodiment has a fish-scale-like deposition morphology, the deposition layer is uniform, dense and flat, and the fish-scale-like structure is the alloy phase surface composed of fine grains.

[0040] The X-ray diffraction pattern of the 1#AlMn negative electrode material prepared in this embodiment was tested. It is hereby explained that in order to reduce the interference of the aluminum foil substrate signal on the analysis results, when preparing the XRD test sample, the positive electrode side of the button-type 2032 battery was assembled with molybdenum foil instead of aluminum foil. Figure 2 The test results show that the diffraction peaks of the deposited layer on the surface of the negative electrode material at 42.1° and 43.9° are consistent with the standard diffraction peaks of Al6Mn (PDF#39-0925), proving that the coating containing the Al6Mn alloy phase is effectively achieved by electrochemical co-deposition.

[0041] For the SCell-1 assembled in step (2) of this example, at a current density of 0.5 mA cm -2 and a deposition capacity of 0.5 mAh cm -2 Under the test conditions, long cycle test is carried out. Figure 3 As shown, the overpotential of the assembled pair of cells under the conditions of this embodiment is 80.9, 51.8 and 51.3 mV respectively at the 50th, 500th and 1000th cycles under the test conditions, showing an ultra-long stable cycle of up to 2000 hours. It is hereby explained that due to the spontaneous formation of an insulating passivation layer on the surface of the aluminum metal, the assembled pair of cells has a higher overpotential in the initial cycle. However, this passivation layer will spontaneously decompose in the ionic liquid electrolyte, so after the first few cycles (the decomposition of the passivation layer occurs in these cycles), the overpotential of the pair of cells remains basically stable.

[0042] For the SCell-1 assembled in step (2) of this example, at a current density of 1 mA cm -2 and a deposition capacity of 1 mAh cm -2 Under the test conditions, long cycle test is carried out. Figure 4 As shown, under the test conditions, the overpotentials of the battery assembled under the conditions of this embodiment at the 50th, 500th and 1000th cycles were 114.4, 90.2 and 94.8 mV respectively, showing an ultra-long stable cycle of up to 2000 h.

[0043] For the FCell-1 assembled in step (3) of this example, at 1Ag -1 The cycle performance test was carried out at a current density of Figure 5 As shown in Figure 2, FCell-1 achieved an ultra-long stable cycle of 3000 cycles under this test condition, during which the average coulombic efficiency was 98.16%. At the 3000th cycle, the discharge capacity was 115.3 mAh g -1 .

[0044] Example 2

[0045] On the basis of Example 1, only the MnCl2 concentration in step (1) is changed to 50mM, the paired battery assembled in step (2) is named SCell-2, and the full battery assembled in step (3) is named FCell-2. The other conditions and steps are consistent with Example 1.

[0046] Take SCell-1 as the sample and set 1mA cm -2 The discharge current density is 3 mAh cm -2 The deposition capacity of the positive electrode side aluminum metal electrode material modified by the electro-deposited alloy coating is named 2#AlMn. The microscopic morphology of the alloy coating on the surface of the positive electrode side aluminum foil was characterized by SEM testing. The test results show that the alloy phase coating obtained in this embodiment has a fish scale-like deposition morphology, and the deposition layer is uniform, dense, and flat. The fish scale-like structure is an alloy phase surface composed of fine grains. Compared with 1#AlMn, the fish scale structure of 2#AlMn prepared in this embodiment is more undulating, and the surface uniformity is reduced.

[0047] For the SCell-2 assembled in step (2) of this embodiment, at a current density of 0.5 mA cm -2 and a deposition capacity of 0.5 mAh cm -2 Under the test conditions, a long cycle test was performed. Under the test conditions, the battery assembled under the conditions of this embodiment showed 177.4, 97.1 and 98.2 mV at the 50th, 500th and 1000th cycles, showing an ultra-long stable cycle of up to 2000 h.

[0048] For the SCell-2 assembled in step (2) of this embodiment, at a current density of 1 mA cm -2 and a deposition capacity of 1 mAh cm -2 Under the test conditions, a long cycle test was performed. Under the test conditions, the overpotentials of the battery assembled under the conditions of this embodiment were 210.5, 135.3 and 137.8 mV at the 50th, 500th and 1000th cycles, respectively, showing an ultra-long stable cycle of up to 2000 h.

[0049] For the FCell-2 assembled in step (3) of this example, at 1Ag -1 The FCell-2 achieved an ultra-long stable cycle of more than 2600 cycles under this test condition, with an average Coulomb efficiency of 97.98%. At the 2600th cycle, the discharge capacity was 112.8 mAh g -1 .

[0050] Example 3

[0051] On the basis of Example 1, the nicotinic acid concentration in step (1) was changed to 1% (mass fraction), the pair of cells assembled in step (2) was named SCell-3, and the full cell assembled in step (3) was named FCell-3. The other conditions and steps were consistent with Example 1.

[0052] Take SCell-3 as the sample and set 1mA cm -2 The discharge current density is 3 mAh cm -2 The deposition capacity of the positive electrode side aluminum metal electrode material modified by the electrochemical co-deposition alloy coating is named 3#AlMn. The microscopic morphology of the alloy coating on the surface of the positive electrode side aluminum foil was characterized by SEM testing. The test results show that the alloy coating obtained in this embodiment has a fish-scale-like deposition morphology, the deposition layer is uniform, dense, and flat, and the fish-scale-like structure is an alloy phase surface composed of fine grains. Compared with 1#AlMn, the grain size in the fish-scale structure of 3#AlMn prepared in this embodiment has increased.

[0053] For the SCell-3 assembled in step (2) of this example, at a current density of 0.5 mA cm -2 and a deposition capacity of 0.5 mAh cm -2 Under the test conditions, a long cycle test was performed. Under the test conditions, the overpotentials of the battery assembled under the conditions of this embodiment were 80.6, 50.3 and 50.9 mV at the 50th, 500th and 1000th cycles, respectively, showing an ultra-long stable cycle of about 2000 h.

[0054] For the SCell-1 assembled in step (2) of this example, at a current density of 1 mA cm -2 and a deposition capacity of 1 mAh cm -2 Under the test conditions, a long cycle test was performed. Under the test conditions, the overpotentials of the battery assembled under the conditions of this embodiment were 108.3, 86.5 and 90.1 mV at the 50th, 500th and 800th cycles, respectively, showing an ultra-long stable cycle of up to 1600 h.

[0055] For the FCell-3 assembled in step (3) of this example, at 1Ag -1 The FCell-3 was tested for cycle performance at a current density of 1.5 volts. Under this test condition, the FCell-3 achieved an ultra-long stable cycle of nearly 2700 cycles, with an average coulombic efficiency of 98.06%. At the 2685th cycle, the discharge capacity was 112.8 mAh g -1 .

[0056] Comparative Example 1

[0057] On the basis of Example 1, when preparing the mixed solution in step (1), only AlCl3 and [EMIm]Cl are prepared into an electrolyte in a molar ratio of 1.3:1, and MnCl2 and nicotinic acid are not added. The paired battery assembled in step (2) is named SCell-0, and the full battery assembled in step (3) is named FCell-0. The other conditions and steps are consistent with Example 1.

[0058] Take SCell-0 as the sample and set 1mA cm -2 The discharge current density is 3 mAh cm -2 The deposition capacity of the positive electrode side aluminum metal electrode material with aluminum metal deposition layer is named 0#AlAl. The SEM test is used to characterize the microscopic morphology of the deposition morphology on the surface of the aluminum foil on the positive electrode side. Figure 6 The test results show the morphology of the deposited layer obtained in this embodiment: the metal aluminum particles are coarse, sparsely distributed, and have clear and sharp edges. This deposition morphology indicates that the battery tends to form coarse aluminum dendrites during the cyclic charge and discharge process, penetrate the diaphragm, and cause the battery to short-circuit.

[0059] For the SCell-0 assembled in step (2) of this embodiment, at a current density of 0.5 mA cm -2 and a deposition capacity of 0.5 mAh cm -2 Under the test conditions, long cycle test is carried out. Figure 3 As shown, under this test condition, the overpotential of SCell-0 at the 50th and 100th cycles was 55.6 and 44.4 mV respectively. It could only cycle stably for about 400 hours before failing due to battery short circuit.

[0060] For the SCell-0 assembled in step (2) of this embodiment, at a current density of 1 mA cm -2 and a deposition capacity of 1 mAh cm -2 Under the test conditions, long cycle test is carried out. Figure 4 As shown, under the test conditions, the overpotential of the battery assembled under the conditions of this embodiment at the 40th cycle was 90.7 mV, and it could only stably cycle for about 100 hours before failing due to battery short circuit.

[0061] For the FCell-0 assembled in step (3) of this example, at 1Ag -1 The cycle performance test was carried out at a current density of Figure 5 As shown in the figure, FCell-0 can only be stably cycled for 392 cycles, during which the average coulombic efficiency is 94.38%. At the 392nd cycle, the discharge capacity is 108.9 mAh g -1 .

[0062] Comparative Example 2

[0063] On the basis of Example 1, nicotinic acid is no longer added when preparing the mixed solution in step (1), the paired battery assembled in step (2) is named SCell-4, and the full battery assembled in step (3) is named FCell-4. The other conditions and steps are consistent with Example 1.

[0064] Take SCell-4 as a sample and set 1mA cm -2 The discharge current density is 3 mAh cm -2 The deposition capacity of the positive electrode side aluminum metal electrode material modified by the deposition layer was named 4#Al-base. The SEM test was used to characterize the microscopic morphology of the deposition morphology on the surface of the aluminum foil on the positive electrode side. The test results show that 4#Al-base has a loose and uneven deposition structure, and the deposited grains are irregular flaky particles. It should be noted that the doping of MnCl2 also plays a role in reducing the charge transfer rate and increasing the nucleation energy barrier, so the size of the 4#Al-base deposition grains has also been significantly reduced (although not as obvious as 1#AlMn).

[0065] For the SCell-4 assembled in step (2) of this embodiment, at a current density of 0.5 mA cm -2 and a deposition capacity of 0.5 mAh cm -2 Under the test conditions, a long cycle test was carried out. At the 10th cycle, the overpotential of SCell-4 was 77.8mV, and it could only cycle stably for 50h before failing due to battery short circuit.

[0066] For the SCell-4 assembled in step (2) of this example, at a current density of 1 mA cm -2 and a deposition capacity of 1 mAh cm -2 Under the test conditions, a long cycle test was carried out. At the 10th cycle, the overpotential of SCell-4 was 83.1mV, and it could only cycle stably for about 30h before failing due to battery short circuit.

[0067] For the FCell-4 assembled in step (3) of this example, at 1Ag -1 The cycling performance test was carried out at a current density of . FCell-4 can only stably cycle for 213 cycles, during which the average coulombic efficiency is 94.17%. At the 213th cycle, the mass specific capacity is 101.4 mAh / g.

[0068] Comparative Example 3

[0069] On the basis of Example 1, only MnCl2 is no longer added when preparing the mixed solution in step (1), the pair of cells assembled in step (2) is named SCell-5, and the full cell assembled in step (3) is named FCell-5. The other conditions and steps are consistent with Example 1.

[0070] Take SCell-5 as the sample and set 1mA cm -2 The discharge current density is 3 mAh cm -2 The deposition capacity of the positive electrode side aluminum metal electrode material with an aluminum metal deposition layer was named 5#Al-base. The SEM test was used to characterize the microscopic morphology of the deposition morphology on the surface of the aluminum foil on the positive electrode side. The test results showed that the deposition morphology of 5#Al-base was uneven, and the deposition layer was composed of coarse semi-lens-shaped deposition particles with a rough surface. It should be noted that this deposition structure indicates that the addition of nicotinic acid promotes the growth of aluminum metal along the interface plane of the aluminum foil, and this conclusion is consistent with the deposition morphology of 1#AlMn and 0#AlAl.

[0071] For the SCell-5 assembled in step (2) of this example, at a current density of 0.5 mA cm -2 and a deposition capacity of 0.5 mAh cm -2 Under the test conditions, a long cycle test was carried out. At the 50th and 100th cycles, the overpotential of SCell-5 was 80.1 and 76.7 mV respectively. It could only cycle stably for about 250 hours before failing due to a battery short circuit.

[0072] For the SCell-5 assembled in step (2) of this example, at a current density of 1 mA cm -2 and a deposition capacity of 1 mAh cm -2 Under the test conditions, a long cycle test was carried out. At the 50th cycle, the overpotential of SCell-5 was 137.5mV, and it could only cycle stably for 128h before failing due to battery short circuit.

[0073] For the FCell-5 assembled in step (3) of this example, at 1Ag -1 The cycling performance test was carried out at a current density of . FCell-5 can only stably cycle for 275 cycles, during which the average coulombic efficiency is 93.98%. At the 275th cycle, the mass specific capacity is 104.8 mAh / g.

[0074] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An aluminum metal negative electrode material with a dynamic alloy coating, characterized in that: The negative electrode material is composed of a two-dimensional current collector or a three-dimensional current collector and an aluminum metal and an aluminum-manganese / aluminum-magnesium based alloy layer on the surface; Among them, the two-dimensional current collector is titanium foil, molybdenum foil, tantalum foil and aluminum foil, the three-dimensional current collector is carbon cloth, carbon paper, titanium mesh, molybdenum mesh, and the composition of the aluminum-manganese alloy layer is Al6Mn.

2. A method for preparing the aluminum metal negative electrode material with a dynamic alloy coating as claimed in claim 1, characterized in that: The method steps are as follows: (1) In a glove box filled with argon, aluminum chloride (AlCl3) and 1-ethyl-3-methylimidazolium chloride ([EMIm]Cl) are prepared into a solution in a certain molar ratio, and then alloying element metal salt and nicotinic acid additive are added to the solution, and magnetic stirring is performed until a transparent and clear mixed solution is obtained; (2) Assembling a CR 2032 button-type battery using the two-dimensional / three-dimensional current collector as the positive and negative electrodes, the mixed solution prepared in step (1) as the electrolyte, and glass fiber as the separator; (3) Using graphite as the positive electrode material, the two-dimensional / three-dimensional current collector as the negative electrode, the mixed solution prepared in step (1) as the electrolyte, glass fiber as the separator, and molybdenum foil to separate the positive electrode material and the gasket, assembling a CR 2032 button-type full battery; Preferably, the molar ratio of AlCl3 to [EMIm]Cl in step (1) is 0.5 to 2:1; Preferably, the alloying element source metal salt in step (1) is MnCl2, MnSO4, Mn(ClO4)2, Mn(NO3)2, MgCl2, MgSO4, Mg(ClO4)2 and Mg(NO3)2; Preferably, the concentration of the alloying element metal salt in step (1) is 10 mM to 100 mM; Preferably, the mass concentration of the nicotinic acid additive in step (1) is 0.5% to 4%.

3. Use of the aluminum metal negative electrode material with a dynamic alloy coating as claimed in any one of claims 1 to 2 in an ionic liquid-based aluminum ion battery negative electrode.